Evolutionary and developmental variation in muscle mitochondrial content - Moyes, Christopher (Henry Stewart Talks, 2007)
Genetic origins of muscle fiber types, Allometric scaling of aerobic metabolism, Role of myonuclear domain in the muscle metabolic phenotype, Post-transcriptional regulation of mitochondrial genes, Coordination of metabolic genes during myogenesis, Metabolic differences among muscles and species, Qualitative variation in mitochondrial design
Archived at 2018/10/28